Identity: Contemporary Identity Politics and the Struggle for Recognition. By Francis Fukuyama. London, UK: Profile Books, 2019, pp. 218, ISBN: 978-1-78125-981-8. - Mohamad Shukri, Syaza Farhana (IIUM Press, International Islamic University Malaysia, 2019)
Famous for his declaration on the end of history after free-market liberal economy triumphed over communism at the end of the Cold War, Francis Fukuyama is back to elucidate on the recent rise of identity politics in the second decade of the twenty-first century. Starting with the vote by the British electorate to leave the European Union, we have seen the rise of more populist leaders such as Donald Trump, Viktor Orban, and Geert Wilders using the rhetoric of identity to rile up voters. While there is a growing body of literature on the subject, what Fukuyama does best is explaining a complex phenomenon in a simple yet elegant prose to make his arguments digestible to a wider audience and thus, helping him make a case on the danger of ignoring identity politics and its roots. ...